Visi Robotika Berbasis Sosial: Memanfaatkan Data Komputer dan Media Sosial untuk Robotika Industri Adaptif - Adjie Bangsawan; Farid, Ahmad; Wijayanto, Maulana; Tsani, Nabilla Mutiara; Wibowo, Yuniar Satrio (Jurnal Ilmiah Sistem Informasi, 2025)
The rapid evolution of industrial robotics has been significantly influenced by the integration of computational data and social media, enabling robots to become more adaptive and responsive in collaborative work environments. This study investigates the role of social media and computational data in enhancing the adaptability of industrial robotics through machine learning techniques. By integrating sentiment analysis from social media with sensor data from industrial robots, this study examines how real-time data functions can improve robot decision-making and human-robot collaboration. Experimental results show a 23% increase in operational efficiency, an 89% accuracy rate in social interaction classification, and a 15% reduction in prediction errors. Furthermore, 62% of public sentiment toward adaptive robots is positive, highlighting the growing acceptance despite concerns over the impact of automation on jobs. These findings suggest that leveraging social media and computational data can significantly enhance the adaptability of robots, leading to a more efficient and socially conscious industrial ecosystem.